1999
DOI: 10.1128/jcm.37.11.3533-3539.1999
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Candida dubliniensis with Commercial Yeast Identification Systems

Abstract: Candida dubliniensis is a newly described species that is closely related phylogenetically to Candida albicans and that is commonly associated with oral candidiasis in human immunodeficiency virus-positive patients. Several recent studies have attempted to elucidate phenotypic and genotypic characteristics of use in separating the two species. However, results obtained with simple phenotypic tests were too variable and tests that provided more definitive data were too complex for routine use in the clinical la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
2
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 26 publications
(48 reference statements)
3
82
2
4
Order By: Relevance
“…On the other hand, chlamydospores of C. albicans occur mostly singly on elongated pseudomycelia (Tintelnot et al 2000). The present findings for growth at 45°C, substrate assimilation profile analysis and production of chlamydospores agree with previous findings for C. dubliniensis reported by Sullivan et al (1997), Pinjon et al (1998), Staib and Morschhauser (1999), Pincus et al (1999) and Giammanco et al (2000). Growth at 45°C has been considered to be a particularly useful test for the differentiation of C. dubliniensis (no growth) from C. albicans (growth) by Pinjon et al (1998).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…On the other hand, chlamydospores of C. albicans occur mostly singly on elongated pseudomycelia (Tintelnot et al 2000). The present findings for growth at 45°C, substrate assimilation profile analysis and production of chlamydospores agree with previous findings for C. dubliniensis reported by Sullivan et al (1997), Pinjon et al (1998), Staib and Morschhauser (1999), Pincus et al (1999) and Giammanco et al (2000). Growth at 45°C has been considered to be a particularly useful test for the differentiation of C. dubliniensis (no growth) from C. albicans (growth) by Pinjon et al (1998).…”
Section: Discussionsupporting
confidence: 90%
“…Growth at 45°C has been considered to be a particularly useful test for the differentiation of C. dubliniensis (no growth) from C. albicans (growth) by Pinjon et al (1998). Although the C. dubliniensis isolates examined did not assimilate a-methyl-D D-glucoside, xylose and DL DL-lactate such non-assimilation is again regarded as a typical property of C. dubliniensis (Gales et al 1999;Pincus et al 1999;Giammanco et al 2000) and the biocode obtained (vide supra) is typical of C. dubliniensis (Giammanco et al 2000;Sullivan et al 1997). In some studies, C. dubliniensis has been differentiated on CHROMagar Candida based on the production of dark green colonies compared with the lighter green colonies of C. albicans (Kirkpatrick et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More accurate discrimination between C. albicans and C. dubliniensis isolates has been achieved by the use of improved carbohydrate assimilation test databases [13] and the application of assays based on the colony morphology of each species when grown on media supplemented with particular plant extracts. For example, when grown on Staib agar (i.e.…”
Section: Clinical Significance Of C Dubliniensismentioning
confidence: 99%
“…to grow at 45°C and Kirkpatrick et al [25] reported an even higher percentage of C. albicans isolates (36%) that failed to grow at this temperature. Pincus et al [20] stated that these variable results may be explained by poor temperature control in incubators or differences in media composition.…”
Section: Growth At Elevated Temperaturesmentioning
confidence: 99%